Islam and Mental Disorders of the Older Adults: Religious Text, Belief System and Caregiving Practices - Suhad Daher-Nashif (10115695) (2022)
This paper illustrates the impact of Islamic religious texts on dementia care in the Middle East. It examines how old age and older adults mental disorders are framed in the Quran and Hadith, and how these texts are transformed to belief ideologies and caregiving practices. The study uses a qualitative research methods, which include a review of all Islamic holy texts that address mental and cognitive changes associated with ageing, along with interviews with eight Sharia scholars and 37-Arab-Muslim families living in Qatar. Islamic texts command compassion and honouring of elderly parents and give care instructions. These texts are transformed into social practices and used as diagnostic and treatment tools. Other Information Published in: Journal of Religion and Health License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s10943-020-01094-5